2000
DOI: 10.1073/pnas.97.1.315
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 3 in the heart transduces not only a hypertrophic signal but a protective signal against doxorubicin-induced cardiomyopathy

Abstract: The signal transducer and activator of transcription (STAT) 3, a transcriptional factor downstream of several cytokines, is activated by Janus kinase families and plays a pivotal role in cardiac hypertrophy through gp130. To determine the physiological significance of STAT3 in vivo, transgenic mice with cardiac-specific overexpression of the Stat3 gene (STAT3-TG) were generated. STAT3-TG manifested myocardial hypertrophy at 12 wk of age with increased expression of the atrial natriuretic factor (ANF), ␤-myosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
169
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(178 citation statements)
references
References 36 publications
8
169
1
Order By: Relevance
“…Several studies support this conclusion. First, STAT proteins have been reported to transduce cardioprotective signals (29,37,83). Although the mediators of this beneficial effect are not defined, interaction of STAT with GATA-4, a cardioprotective transcription factor (3), and activation of ANF and/or VEGF may explain at least part of STAT cardioprotective effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies support this conclusion. First, STAT proteins have been reported to transduce cardioprotective signals (29,37,83). Although the mediators of this beneficial effect are not defined, interaction of STAT with GATA-4, a cardioprotective transcription factor (3), and activation of ANF and/or VEGF may explain at least part of STAT cardioprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Others found that overexpression of STAT3 leads to cardiac hypertrophy but also protects against druginduced cardiotoxicity (37). More recently, mice with cardiacspecific inactivation of STAT6 were generated and found to have an impaired response to pressure overload (29).…”
mentioning
confidence: 99%
“…Generation of Transgenic Mice Expressing STAT3 Mutants-Transgenic mice with cardiac-specific overexpression of the caSTAT3 gene, caSTAT3 TG, were generated as described previously (15). caSTAT3 cDNA was subcloned into SalI site of pBSIISK(ϩ)-␣-MHC plasmid, a kind gift from Dr. J. Robbins (Children's Hospital, Cincinnati, OH) (25).…”
Section: Methodsmentioning
confidence: 99%
“…The stimulation of GP130 activates Janus kinase/STAT, mitogen activated protein kinase, and phosphatidylinositol 3-kinase/Akt pathways (11,12). The signals through GP130 transduce cell survival signals as well as hypertrophic signals (13)(14)(15)(16). Mice with GP130 gene knocked out in a cardiac-specific manner showed the decompensation in response to pressure overload (17), suggesting that the GP130/Janus kinase/STAT pathway is critical for adaptation in response to extracellular stresses.…”
mentioning
confidence: 99%
“…STAT3 seems to be crucial to maintaining cardiac capillary density through several mechanisms, including direct regulation of VEGF expression, induction of proangiogenic cytokines and suppression of anti-angiogenic gene programmes in the heart. Mice lacking STAT3 in the heart are also more susceptible to doxorubicin-induced cardiotoxicity, and overexpression of STAT3 protects against this [85][86][87] . Although JAK1 or tyrosine kinase 2 (TYK2) might be able to compensate for the inhibition of JAK2 in the heart (JAK3 is not expressed), these findings raise concerns about possible cardiotoxicity of JAK2 inhibitors, particularly if they have activity against several JAK family kinases.…”
Section: Sorafenibmentioning
confidence: 99%